Sistem Pendukung Keputusan Penentuan Guru Terbaik Menggunakan Metode - Addinul, Ahmad; Addinul Haq, Ahmad (Journal Information Technology Trends (JITRENDS), 2024)
The Regional Technical Implementation Unit (UPTD) of Sekolah Menengah Pertama (SMP) Negeri 1 Bati – Bati is a secondary education institution under the Ministry of Education and Culture, heavily relying on the quality of its teachers' performance for smooth learning processes. Currently, the school has not implemented a system for evaluating teacher performance, including the selection of the best teacher, resulting in the absence of a mechanism to determine the best teacher. To address this issue, a Decision Support System (DSS) using the Multi- Objective Optimization by Ratio Analysis (MOORA) method is proposed. This DSS is designed using an Entity Relationship Diagram (ERD) for database design, Unified Modeling Language (UML) for system modeling, and interface design. The DSS was tested using blackbox testing and accuracy testing, where the blackbox testing achieved a 100% success rate from 15 scenarios tested, and the accuracy testing reached a 100% accuracy rate. The DSS is expected to minimize the time required in the process of determining the best teacher at UPTD SMP Negeri 1 Bati – Bati.